Halogenated Indole Alkaloids from Marine Invertebrates - Pauletti, Patrícia Mendonça (Molecular Diversity Preservation International, 2010)
This review discusses the isolation, structural elucidation, and biological activities of halogenated indole alkaloids obtained from marine invertebrates. Meridianins and related compounds (variolins, psammopemmins, and aplicyanins), as well as aplysinopsins and leptoclinidamines, are focused on. A compilation of the (13)C-NMR spectral data of these selected natural indole alkaloids is also provided.